Analgesic Effects of Ultrasound‐Guided Iliohypogastric/Ilioinguinal Nerve Block Combined with Lateral Femoral Cutaneous Nerve Block in Total Hip Arthroplasty via Direct Anterior Approach: A Retrospective Cohort Study. Issue 3 (31st March 2021) - Wang, Qiuru; Yang, Yong; Yang, Zhouyuan; Hu, Yunlian; Zhao, Xin; Chen, Changjun; Kang, Pengde
Abstract : Objective: This study aimed to explore the efficacy and safety of the combination of lateral femoral cutaneous nerve blocks (LFCNB) and iliohypogastric/ilioinguinal nerve blocks (IHINB) on postoperative pain and functional outcomes after total hip arthroplasty (THA) via the direct anterior approach (DAA). Methods: In this retrospective cohort study, patients undergoing THA via the DAA between January 2019 and November 2019 were stratified into two groups based on their date of admission. Sixty‐seven patients received LFCNB and IHINB along with periarticular infiltration analgesia (PIA) (nerve block group), and 75 patients received PIA alone (control group). The outcomes included postoperative morphine consumption, postoperative pain assessed using the visual analogue scale (VAS), the QoR‐15 score, and functional recovery measured as quadriceps strength, time to first straight leg rise, daily ambulation distance, and duration of hospitalization. The Oxford hip score and the UCLA activity level rating were assessed at 1 and 3 months after surgery. In addition, postoperative complications were recorded. Patients were also compared based on the type of incision used during surgery (traditional longitudinal or "bikini" incision). Results: Patients in the nerve block group showed significantly lower postoperative morphine consumption, lower resting VAS scores within 12 h postoperatively, lower VAS scores during motion within 24 h postoperatively, and better QoR‐15 scores on postoperative day 1. These patients also showed significantly better functional recovery during hospitalization. At 1‐month and 3‐month outpatient follow up, the two groups showed no significant differences in Oxford hip score or UCLA activity level rating. There were no significant differences in the incidence of postoperative complications. Similar results were observed when patients were stratified by type of incision, except that the duration of hospitalization was similar. Conclusion: Compared to PIA alone, a combination of LFCNB and IHINB along with PIA can improve early pain relief, reduce morphine consumption, and accelerate functional recovery, without increasing complications after THA via the DAA. Abstract : The location of the iliohypogastric nerve (IHN), the ilioinguinal nerve (IIN), and the lateral femoral cutaneous nerve (LFCN) (A). Schematic diagram of the location of the nerve block (B). The upper block is the iliohypogastric/ilioinguinal nerve block (IHINB) and the lower block is the lateral femoral cutaneous nerve block (LFCNB). The blue box shows the position of the ultrasonic transducer and the symbol x shows the needle insertion point. ASIS, anterior superior iliac spine. Schematic diagram of the IHINB (A). The high‐frequency linear‐array ultrasonic transducer was placed perpendicular to the inguinal ligament, with the lower end of the transducer at the ASIS and the upper end facing the umbilicus. The needle was inserted under the transducer from lateral to medial side in‐plane. Schematic diagram of the LFCNB (B). The transducer was placed on the inguinal ligament, with the upper end above the ASIS and the lower end pointing to the pubic symphysis. Then the transducer was moved along the inguinal ligament slowly inward and downward until the LFCN was detected. The needle was inserted from lateral to medial side in‐plane.